Pendampingan Psikologis pada Siswa SMK di Kendal untuk Mengurangi Depresi akibat Pembelajaran Daring di Masa Pandemi - Very Julianto; Nandia Putri Zuhdi Almakhi (Indonesia Berdaya, 2021)
The Covid-19 pandemic has prompted the government to implement various policies, including online learning policies in the education field. Although it has some advantages, online learning also has a negative impact, especially on the student’s psychological condition. The findings showed that students experienced a lot of depression during online learning in pandemic times. Students can experience depression due to prolonged psychosomatic disorders that are not treated immediately. The study was conducted with the aim of lowering students’ levels of depression during online learning through psychological mentoring. The mentoring model used is the service-learning model with one group pre-post test measurement design. The mentoring group consisted of 30 students. Measurement of depression levels is done with the Depression, Anxiety, and Stress Scale (DASS). The results showed a difference between the students’ depression levels before and after mentoring (F=6,073; p less than 0.05). The result of this mentoring is students can lower their depression levels due to online learning through psychological mentoring.Abstrak. Pandemi Covid-19 mendorong pemerintah untuk menerapkan berbagai kebijakan, termasuk kebijakan pembelajaran daring dalam bidang pendidikan. Meskipun memiliki beberapa kelebihan, pembelajaran daring juga memiliki dampak negatif terutama pada kondisi psikologis siswa. Temuan menunjukkan bahwa siswa banyak mengalami depresi selama pembelajaran daring di masa pandemi. Siswa dapat mengalami depresi karena adanya gangguan-gangguan psikosomatis berkepanjangan yang tidak segera ditangani. Pendampingan ini dilakukan dengan tujuan untuk menurunkan tingkat depresi siswa selama pembelajaran daring melalui pendampingan psikologis. Model pendampingan yang digunakan adalah service learning dengan desain pengukuran one group pre-post test. Kelompok pendampingan terdiri dari 30 siswa SMK. Pengukuran tingkat depresi dilakukan dengan Depression, Anxiety, and Stress Scale (DASS) subtes Depresi. Hasil menunjukkan perbedaan tingkat depresi siswa sebelum dan sesudah pendampingan (F=6,073; p kurang dari 0.05). Hasil dari pendampingan ini adalah siswa dapat menurunkan tingkat depresi akibat pembelajaran daring melalui pendampingan psikologis.